Can theosis deradicalize Christian fundamentalism? - Aristo Purboadji (Cogent Arts & Humanities, 2023)
There has been a lot of concerns about the rise of fundamentalism in Christianity lately, especially since the January 6 Capitol Hill storming, that many see as the line in the sand as far as far-right is concerned. Consequently, the need to deradicalize that particular group within Christianity has been brought up to the fore. This study suggests that the doctrine of theosis can be utilized as Religious-Education-form of Deradicalization of Christian fundamentalism as has been done by Papanikolaou , whose work I view as an effort to deradicalize the Radical Orthodoxy in its rejection of liberal democracy. This study concludes that theosis combined with hermeneutics of charity has the potential to deradicalize five fundamentalism mindsets within Christianity and advocates it beyond Orthodoxy.